Pyrimidine Carboxylic Acids Linked through 1,4,5-Trisubstituted 1,2,3-Triazoles: Synthesis and RNase A Inhibition Studies - Chakraborty, Kaustav; Dasgupta, Swagata; Pathak, Tanmaya (Synlett, 2025)
A series of triazolylated nucleoside carboxylic acid derivatives have been synthesized using a 1,3-dipolar cycloaddition reaction. The ribonuclease A (RNase A) inhibitory properties of the synthesized molecules have been studied by experimental and theoretical techniques. The compounds were found to inhibit RNase A in a reversible competitive manner. The inhibitory potency was significantly enhanced by the incorporation of a larger number of carboxylic acid groups in the inhibitor. A theoretical justification of the observed results was provided by an investigation of the docked structures of the enzyme–inhibitor complexes.
Keywords: pyrimidinecarboxylic acids; triazoles; ribonuclease A; 1,3-dipolar cycloaddition; enzyme inhibitor; docking studies